Development of Heutagogy Learning Module for Mastering Thinking Skills in Industrialized Building System Course - Ahmad Hazari, Nor Nabilah; Yee, Mei Heong (Research and Innovation in Technical and Vocational Education and Training, 2022)
This study is a Development of Heutagogy Learning Module for Mastery of Thinking Skills for Industrial Building Systems (IBS) Course. The main objective of this study was to develop a heutagogy learning module for the mastery of thinking skills for IBS courses for students and teachers of Construction Technology in Vocational Colleges. This module is developed based on the ADDIE Model. The instrument used in this study was to collect data through feedback forms given to teachers and students of Vocational Colleges. This study uses the dichotomy scale method to obtain information from respondents. The results of the analysis performed show a positive result that the Heutagogy Learning Module for the mastery of Thinking Skills for the Industrial Building Systems (IBS) course developed is suitable and adapted for the use of teachers and students. However, some weaknesses exist in the development of this module due to the researcher himself who is the first experience in the module developed. Nevertheless, this study can be further developed despite its shortcomings. Among the researcher's suggestions for the future is to develop more complete modules for all topics in the Industrial Building Systems (IBS) course by applying heutagogy learning methods.